Time-dependent condensation of bosonic potassium - Kabelac, Anton; Wolschin, Georg (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2022)
We calculate the time-dependent formation of Bose-Einstein condensates (BECs) in potassium vapours based on a previously derived exactly solvable nonlinear boson diffusion equation (NBDE). Thermalization following a sudden energy quench from an initial temperature $$T_i$$to a final temperature $$T_f$$below the critical value and BEC formation are accounted for using closed-form analytical solutions of the NBDE. The time-dependent condensate fraction is compared with available $$^{39}